Simulation of Bulk Metal Forming by Means of Finite Integral Mesh Free Methods - Li, C. S.; Xiong, S. W.; Rodrigues, J. M. C.; Martins, P. A. F. (Proceedings of the Institution of Mechanical Engineers. Part C, Journal of mechanical engineering science, 2005)
Abstract This paper draws from the fundamentals of the finite integral mesh free representation methods and of the rigid-plastic formulation for slightly compressible materials to the main aspects of computer implementation and modelling of bulk-metal forming processes. Fundamental research and development is based on the reproducing kernel particle method (RKPM) and the corrected smoothed particle hydrodynamics (CSPH) method. Special emphasis is placed on a wide range of theoretical and numerical subjects such as discretization procedures, numerical integration of the system matrices derived from the weak form, relief of volumetric locking, geometrical update of the deforming workpiece, and treatment of the frictional contact interface between the workpiece and tooling.